THE ROLE OF INTERNAL AUDIT IN EFFORTS TO REALIZE GOOD CORPORATE GOVERNANCE (CASE STUDY AT PT BANK MANDIRI (PERSERO) TBK. AMBON BRANCH OFFICE) - Kevin H Tupamahu; Syahrina Noormala Dewi; Ingrid Waitatta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research discusses the Role of Internal Audit in Efforts to Achieve Good Corporate Governance (Case Research at PT Bank Mandiri (Persero) Tbk. Ambon Branch Office). The problem in this thesis is how the implementation of Good Corporate Governance at PT Bank Mandiri (Persero) Tbk Ambon Branch Office, how is the role of internal audit in an effort to realize Good Corporate Governance at PT Bank Mandiri (Persero) Tbk Ambon Branch Office, how can internal audit benefit Good Corporate Governance at PT Bank Mandiri (Persero) Tbk Ambon Branch Office. The type of research used in this research is descriptive research with a qualitative approach. The data were obtained from the interview process, and then reduced, and the data was presented, after which the data was verified. The results of this research indicate that the role of internal audit in an effort to achieve good corporate governance in PT. Bank Mandiri (Persero) Tbk. Ambon Branch Office where the implementation of Good Corporate Governance at PT Bank Mandiri (Persero) Ambon Branch Office has been carried out well, socialized by letter and has been monitored by its implementation and always evaluates employee performance and at least four times a year, HR also always does employee development and it is carried out continuously, employee development in the form of being given training, consulting assistance, and discussions. Internal audit certainly provides the benefits of Good Corporate Governance at PT Bank Mandiri (Persero) Ambon Branch Office in the form of being able to increase points from year to year regarding good corporate governance (GCG) because internal audit provides recommendations for improvements and objective information about the activities being examined at all levels management so that there is an increase in achieving company goals.